2015
DOI: 10.3892/or.2015.3996
|View full text |Cite
|
Sign up to set email alerts
|

miR-193b acts as a cisplatin sensitizer via the caspase-3-dependent pathway in HCC chemotherapy

Abstract: Mounting evidence suggests that microRNAs (miRNAs) play important roles in the development of cancer by targeting expression of tumor-related genes. In the present study, downregulation of miR-193b was observed in hepatocellular carcinoma (HCC) tissues and HCC cell lines by quantitative RT-PCR analyses, suggesting that miR-193b is a tumor-suppressor in HCC. More importantly, miR-193b significantly enhanced the cytotoxicity of cisplatin in HepG2 cells by targeting Mcl-1. Knockdown of the Mcl-1 gene by specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…Several of the differentially expressed miRNAs identified here were previously shown to be involved in diverse stress responses including apoptosis and senescence, further validating the specificity of our screen [ 16 , 29 , 38 40 ]. For the following reasons we focused our attention mainly on the function of miR-30e.…”
Section: Discussionsupporting
confidence: 81%
“…Several of the differentially expressed miRNAs identified here were previously shown to be involved in diverse stress responses including apoptosis and senescence, further validating the specificity of our screen [ 16 , 29 , 38 40 ]. For the following reasons we focused our attention mainly on the function of miR-30e.…”
Section: Discussionsupporting
confidence: 81%
“…MiR-193b was found to be downregulated in hepatocellular carcinoma. Enforced expression of miR-193b significantly enhanced the curative effect of cisplatin 26 . Combination treatment with tamoxifen and anti-miR-181b or anti-miR-221 proved to reduce breast tumor size 27 .…”
Section: Discussionmentioning
confidence: 96%
“…In addition, plenty of researches showed that the expression level of MCL-1 determines the sensitivity of multiple cancers to cisplatin. For instance, microRNA-193b enhances the cytotoxicity of cisplatin to hepatocellular carcinoma cells by targeting Mcl-1 [13]. Imperatorin acts as a cisplatin sensitizer via down-regulating MCL-1 expression in HCC chemotherapy [14].…”
Section: Introductionmentioning
confidence: 99%